Dampak Revolusi Industri 4.0 Terhadap Pengembangan Sumber Daya Manusia (Studi Pada Karyawan Divisi Produksi PT. Gunung Agung Sentosa/ Luckystar Gresik) - Muhammad Azzam Lazuardi; Muhammad Alkirom Wildan (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
Technological developments in the industrial era brought many changes, especially in the world of work. This study aims to determine the impact of the industrial revolution 4.0 in the company's operational changes to the development of human resources in the production division of PT. Gunung Agung Sentosa (Luckystar) The resource person in this study is the head of the production division. Researchers used 10 research items to see how the impact of the 4.0 industrial revolution that occurred in the company's operational changes on the development of human resources in the production division of PT. Mount Agung Sentosa (Luckystar) Gresik. The data collection technique used in this research is to make observations, interviews, and documentation. What is done indirectly is the researcher with the head of the production division and the state of human resources in the production division environment considering the conditions of the covid-19 pandemic that occurred. The results of this study indicate that the impact of the industrial revolution 4.0 provides negative and positive changes with the development of technology given to the operations of the production division of PT. Mount Agung Sentosa.